Reconceptualizing libraries : perspectives from the information and learning sciences - Lee, Victor R.; Phillips, Abigail L. (New York, NY : Routledge, 2019)
"Reconceptualizing Libraries brings together cases and models developed by experts in the information and learning sciences to explore the potential for libraries to adapt and transform in the wake of new technologies for connected learning and discovery. Chapter authors explore the ways that the increased interest in the design research methods, digital media emphases, and technological infrastructure of the learning sciences can foster new collaborations and formats for education within physical library spaces. Models and case studies from a variety of library contexts demonstrate how library professionals can act as change agents and design partners, and how patrons can engage with these evolving experiences. This is a timely and innovative volume for understanding how physical libraries can incorporate and thrive as educational resources using new developments in technology and in the learning sciences"--
Libraries will be essential to the smart and connected communities of the future / Victor R. Lee -- Makerspaces in libraries: social roles and community engagement / Kyungwon Koh, June Abbas, and Rebecca Willett -- Making connected messages: designing community-relevant murals with youth in public libraries / Yasmin Kafai, Orkan Telhan, Richard Lee Davis, K-Fai Steele, and Barrie Adleberg -- Building expansive family STEAM programming through participatory design research / Carrie Tzou, Philip Bell, Megan Bang, Rekha Kuver, Amy Twito, and Ashley Braun -- Designing alternate reality games for the public library's summer reading programs / Elizabeth Bonsignore, Derek Hansen, and Kari Kaus -- Improving digital experience through modeling the human experience: the resurgence of virtual (& augmented & mixed) reality / Diana Hellyar, Renee Walsh, and Micah Altman -- Designing for STEM in libraries serving underserved communities / Crystle Martin -- Redefining mentorship in facilitating interest-driven learning in libraries / Tamara Clegg and Mega Subramaniam -- Small town librarians as experience engineers / Abigail L. Phillips, Victor R. Lee, and Mimi Recker -- Cultivating school librarian discernment as E-learning technology stewards of the future / Rebecca Reynolds and Chris Leeder -- The design of digital learning activities for libraries through participatory design / Jason Yip and Kung Jin Lee -- Probing causal relationships between what school librarians do and what learners gain in school libraries: a reconceptualization of the profession's research agenda / Marcia Mardis, Faye R. Jones, Lenese Colson, Shana Pribesh, Sue Kimmel, Barbara Schultz-Jones, Laura Pasquini, and Laura Gogia -- Using research-practice partnerships to support interest-related learning in libraries / William R. Penuel, Josephina Chang-Order, and Vera Michalchik -- Learning through new experiences: a researcher of modern-day librarianship discovers the learning sciences / Abigail L. Phillips -- Looking Back to See Forward / Beth Yoke.
Includes bibliographical references.
AAL
Parama
Keywords: Libraries and education; Libraries and community; Libraries -- Information technology